2018
DOI: 10.1111/andr.12512
|View full text |Cite
|
Sign up to set email alerts
|

Human tissue kallikrein 1 ameliorates erectile function via modulation of macroautophagy in aged transgenic rats

Abstract: Previously, we have demonstrated that human tissue kallikrein 1 (hKLK1) improves age-related erectile dysfunction (ED). Autophagy has been implicated in age-related diseases, including ED. However, the molecular mechanisms underlying hKLK1-mediated amelioration of age-related ED via regulation of autophagy remains unknown. To explore the potential mechanism, male wild-type Sprague-Dawley rats (WTR) and transgenic rats harboring human KLK1 (TGR) were bred till 4 or 18 months of age and divided into three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…29,30 Factors leading to ED may result from impaired erection or the disruption of normal penile components. 31 Aging has been recog- injury 18 and Nrf2/Keap-1 pathway has been reported to play an important role in the mechanism against oxidative damage. 19 These two pathways were also reconfirmed their role in AED.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Factors leading to ED may result from impaired erection or the disruption of normal penile components. 31 Aging has been recog- injury 18 and Nrf2/Keap-1 pathway has been reported to play an important role in the mechanism against oxidative damage. 19 These two pathways were also reconfirmed their role in AED.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a programmed process in which the cell swallows and degrades the cytoplasmic contents to supplement metabolic needs . Previous studies showed that enhanced autophagy could alleviate the fibrosis process of the corpus cavernosum and thus improve erectile function . In this study, autophagy in the corpus cavernosum was enhanced in DMED rats, which might be because of the compensatory autophagy enhancement to clear the damaged cell structures.…”
Section: Discussionmentioning
confidence: 54%
“…Autophagy is a self‐regulating mechanism for cells to obtain nutrients needed to maintain survival and is also an important self‐regulating system for cells to inhibit apoptosis and fibrosis. Previous studies have reported the autophagic change in the CC associated with ageing, hyperlipidaemia and diabetes‐induced ED (Li, Cui, et al., 2017; Tang et al., 2018; Zhang et al., 2019). However, to our knowledge, this is the first report of autophagy in the CC of a rat with BCNI.…”
Section: Discussionmentioning
confidence: 94%